Українська відеопоезія як естетичний феномен сучасного літературного процесу - Романенко, Олена Віталіївна (Київський національний університет імені Тараса Шевченка, 2022)
The results of the study of video poetry as a genre are presented. The object of analysis is Ukrainian video poetry, created within the projects CYCLOP (Ukraine), "Overcoming Silence" (Ella Yevtushenko, Daryna Gladun, Lesyk Panasyuk, and others), #DigitalShevchenko, "Power of Speech", "Subjective" (Sofia Bezverkha and Marichka Yarmola), "rosdilovi" (Olga Mykhailyuk and Serhiy Zhadan), "By the way" (Natalia Parshchyk, etc.), ZEBRA festival (Germany). Ukrainian video poetry has been developing since the 2000s and was first presented as part of the CYCLOP festival, which became both a venue for a video poetry competition and a platform for theoretical discussions. The significance of poetic intonation and the interaction of reader and author in video poetry is described. Genre features of video poetry are established, and also types of genre transformation are allocated. It has been proved that video poetry is a syncretic multimedia genre, which combines verbal and nonverbal components. The verbal component is the voice of the reader or poet, as well as the melody that complements them. The non-verbal component is based on the development of a visual metaphor or game plot, it also expresses the perception of images, metaphors, etc. poem. The movement of frames in video poetry is based either on the metric-rhythmic identity of the poem (and the melody that accompanies the reading of poetry) and the video sequence, or the dissonance between the verbal and nonverbal components. Genre features of video poetry can be described as a combination of kinetic images, sound, visual metaphors, the voice of the reader, melody, and others. Genre transformations of video poetry are defined through the creation through animation, feature film script, improvisational transformation, and interaction between different arts or the use of digital technology. It is determined that an important aspect of video poetry is the interaction of the author and the recipient. Watching video poetry, on the one hand, actualizes the associations (verbal and nonverbal) in the memory of the recipient, on the other – enhances the aesthetic experience of perception of the work. It gives a powerful aesthetic and emotional effect.

Представлено результати вивчення відеопоезії як жанру. Об'єктом аналізу є українська відеопоезія, створена у межах проєктів CYCLOP (Україна), "Долаючи тишу" (Елла Євтушенко, Дарина Гладун, Лесик Панасюк та ін.), #DigitalShevchenko, "Сила слова", "Суб'єктив" (Софія Безверха і Марічка Ярмола), "розділові" (Ольга Михайлюк та Сергій Жадан), "До слова" (Наталія Парщик та ін.), фестивалю ZEBRA (Німеччина). Українська відеопоезія розвивається з 2000-х рр., і спочатку була представлена в межах фестивалю CYCLOP, який став і місцем конкурсу відеопоезії, і майданчиком для теоретичних дискусій. Описано значущість поетичної інтонації, взаємодії читача й автора у відеопоезії. Установлено жанрові особливості відеопоезії, а також виділено типи жанрової трансформації. Доведено, що відеопоезія – це синкретичний мультимедійний жанр, у якому поєднуються вербальний і невербальний складники. Вербальний складник – це голос читця або поета, а також мелодія, яка їх доповнює. Невербальний складник заснований на розгортанні візуальної метафори чи ігрового сюжету, він також увиразнює сприйняття образів, метафор та ін. вірша. Рух кадрів у відеопоезії заснований або на метрико-ритмічній тотожності вірша (і мелодії, яка супроводжує читання поезії) і відеоряду, або дисонансі між вербальним і невербальним складником. Жанрові особливості відеопоезії можна описати як поєднання кінетичних зображень, звуку, візуальних метафор, голосу читця, мелодії й ін. Жанрові трансформації відеопоезії визначаються через створення за допомогою анімації, сценарію ігрового кіно, перетворення на засадах імпровізації та взаємодії між різними видами мистецтва або застосування цифрових технологій. Визначено, що важливим аспектом відеопоезії є взаємодія автора й реципієнта. Перегляд відеопоезії, з одного боку, актуалізує асоціації (вербальні і невербальні) у пам'яті реципієнта, з іншого – посилює естетичні переживання сприйняття твору. Це дає потужний естетичний і емоційний ефект.
Ukrainian video poetry as an aesthetic phenomenon of the modern literary process
Keywords: відеопоезія; жанр; жанрові трансформації; візуальна метафора; читець; українська література; video poetry; genre; genre transformations; visual metaphor; reader; Ukrainian literature